Sustainable Biochar–Covalent organic framework (COF) hybrids for selective remediation of lead and arsenic from groundwater - Abeer Adaileh; Eman Fayad; Mohammad Abu Shuheil; Eslam A. Mohamed; Dalal Nasser Binjawhar; H.A. Abdel Samad; Mahmoud F. Mubarak (Biomass and Bioenergy, 2026)

Clarifying the effects of copper and cadmium stress on sea bass (Dicentrarchus labrax): implications for tissue bioaccumulation, stress biomarkers, and antioxidant-immune-related genes - Mahmoud Radwan; Moussa A. Moussa; Mohamed Fares; Wafa Abdullah I. Al Megrin; Shahd Yassir; Mohammad R. K. Abdel-Samad (Veterinary Research Communications, 2026)

Dynamic regulation of porcine luteal physiology by fibroblast growth factors: expression patterns and FGF2 modulation in-vitro - Rishi Nanda; V. S. Chouhan; Poonam Yadav; H. A. Samad; Sanjib Borah; Simson Soren; Devojyoti Dutta; V. P. Maurya; Gyanendra Singh (Veterinary Research Communications, 2026)

Progress in plant-derived terpenoid: biosynthetic pathways, therapeutic roles, and sustainable production strategies - Abdul Fatah A. Samad; Nazrin Abd-Aziz; Joazaizulfazli Jamalis; Mohd Bakri Bakar; Azman Abd Samad; Raihana Ridzuan; Siti Ernieyanti Hashim; Alina Wagiran; Mira Panadi; Mohd Ridzuan Mohd Abd Razak (Phytochemistry Reviews, 2026)

The ecology and evolution of cues and signals in animal interspecies cooperation - K. Dunkley; M. Cantor; A.I. Afan; D.S. Ahlibi; S.J. Allen; J. Amphaeris; S. Atkins; M.C. Attwood; K. Bankhead; C.J. Blair; J.L. Bronstein; Y.R.R. Camargo; et al. (Animal Behaviour, 2026)

A two-stage GIS–MCDM framework for wave energy farm site selection – A case study in Sri Lanka - H.D. Suriarachchi; R.L.K. Lokuliyana; A. Samad; H.C.P. Karunasena (Ocean Engineering, 2026)

Antibacterial activity of bioactive anthraquinones isolated from Cassia tora L. against pathogenic intestinal microorganisms - Sri Renukadevi Balusamy; Seungah Lee; Gokulanathan Anandapadmanaban; Abdus Samad; Md Ripon Shikder; Chinnadurai Veeramani; Mohammed A. Alsaif; Khalid S. Al-Numair; Priyanka Singh; Haribalan Perumalsamy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Antimicrobial resistance (AMR) poses a major global health challenge, particularly in intestinal infections where the efficacy of conventional antibiotics is rapidly declining. The rising prevalence of antibiotic-resistant pathogens underscores the urgent need for alternative antimicrobial agents with favorable activity profiles. This study evaluated the antibacterial potential of bioactive anthraquinones isolated from Cassia tora L. seeds against clinically relevant intestinal pathogens and probiotic bacteria. Five key anthraquinones, rhein, physcion, anthraquinone-2-carboxylic acid, emodin, and aloe-emodin, were identified and tested for their antibacterial activity. The anthraquinone metabolites exhibited strong antibacterial activity against pathogenic bacteria ( Escherichia coli , Staphylococcus aureus , Clostridium difficile , etc.), while showing moderate to relatively lower inhibitory effects against beneficial probiotic strains such as Clostridium butyricum , Bifidobacterium bifidum , and Lactobacillus casei . The MIC profiles indicate relative or modest selectivity toward pathogens, rather than a complete sparing of probiotic species. Molecular docking analysis revealed that these metabolites bind favorably to key bacterial resistance proteins, often surpassing ciprofloxacin in binding affinity, supporting their observed antibacterial activity. Together, these results suggest that C. tora anthraquinones preferentially inhibit intestinal pathogens, maintaining a comparative margin of safety for beneficial gut flora. Anthraquinones isolated from C. tora seeds exhibit potent antibacterial activity toward pathogenic intestinal bacteria and relatively reduced activity against probiotic strains, reflecting selective preference in intestinal bacteria. These findings support their potential as natural antimicrobial candidates for managing intestinal infections and contributing to AMR mitigation. Nonetheless, the measurable inhibitory effects on probiotic species emphasize the need for careful dose optimization and microbiome-conscious therapeutic strategies. Further studies focusing on the mechanism of action, pharmacokinetics, toxicity, and in vivo efficacy are required to evaluate their clinical applicability.

Ultrastructure of midgut, Malpighian tubules, testis, and ovariole of adult superworm Zophobas morio (Fabricius, 1776) (Coleoptera: Tenebrionidae) - Lamia M. El-Samad; Helmy A. Aamer; Mariam H. Youssef; Özyurt Koçakoğlu Nurcan; Candan Selami; Neama A. Aamer (Zoomorphology, 2026)

Neuroprotective efficacy of royal jelly and propolis against cadmium-induced dysregulation of neurogenesis and neurotransmitters in the brain of rats: Molecular mechanisms and ultrastructure investigations - Norhan S. El-Sayed; Eman M. Omar; Esraa S. Habiba; Sahar A. Harby; Amany Attaallah; Maria Augustyniak; Abeer El Wakil; Lamia M. El-Samad; Mohamed A. Hassan (Journal of Trace Elements in Medicine and Biology, 2025)

Cynanchum acutum L. ethanolic fruit extract induces cell-cycle arrest and apoptosis in HepG2 human liver cancer cells via programmed cell death signaling pathways - Md Abdus Samad; Iftikhar Ahmad; Sameer Ahmad; Torki A. Zughaibi; Mohammad Hassan Alhashmi; Alaa M.S. Khedr; Fahad A. Al-Abbasi; Samina Wasi; Shams Tabrez (Biocatalysis and Agricultural Biotechnology, 2025)

Biomonitoring brick kiln pollution in Egypt: Neurotoxic and oxidative stress responses in Blaps polychresta beetles as indicators of air and soil contamination - Lamia M. El-Samad; Helmy A. Aamer; Azza A. Atia; Doha H. El-Gashingy; Neama A. Aamer (Science of The Total Environment, 2025)

Advancing alkaloid-based medicines: medical applications, scalable production and synthetic innovations - Siti Ernieyanti Hashim; Norazah Basar; Azman Abd Samad; Shajarahtunnur Jamil; Mohd Bakri Bakar; Joazaizulfazli Jamalis; Nazrin Abd-Aziz; Alina Wagiran; Mohd Ridzuan Mohd Abd Razak; Abdul Fatah A. Samad (Phytochemistry Reviews, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Therapeutic effects of Euphorbia altissima on excisional wound model: role of apoptosis, oxidative stress, and inflammatory molecules - Hanan Ibrahim Althagbi; Khalid M. Alqaisi; Noralhuda Ayad Ibrahim; Parween Abdul-Samad Ismail; Ahmed A. J. Jabbar; Rawaz Rizgar Hassan; Muzhda Haydar Saber; Ahmed Hameed Al-Dabhawi; Goran Noori Saleh; Talal Salem Al-Qaisi (Journal of Molecular Histology, 2025)

Neuroprotective effect of niacin in a rat model of obesity induced by high-fat-rich diet - Natasha Manzoor; Noreen Samad; Sheraz Ahmed Bhatti; Ali Irfan; Sadaf Ahmad; Gamal A. Shazly; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Statistical factorial design for optimum reduction of tellurite and production of tellurium nanostructure by a novel strain Phytobacter diazotrophicus Te1 - Alaa A. Abdel-Samad; Mohamed Ismaeil; Einas H. El-Shatoury; Ali M. Saeed (Archives of Microbiology, 2025)

Constructing a novel Z-scheme Fe2O3/ZnIn2S4@Bi2WO6 photocatalyst for boosting removal of non-biodegradable ciprofloxacin and long-term stable CO2 conversion - Jie Huang; Ali B.M. Ali; Amal Abdulrahman; Abdul Amir H. Kadhum; Sarminah Samad; Haitham Osman; M.A. Diab; Mukhtorjon Karimov; Heba A. El-Sabban; Elyor Saitov (Journal of Water Process Engineering, 2025)

Investigating the influence of antagonistic fungi Polydomus karssenii and Niesslia gamsii on the penetration of Heterodera filipjevi and Pratylenchus thornei in wheat - Osameh Atiya; Samad Ashrafi; Abdelfattah A. Dababat; Wolfgang Maier; Halil Toktay (Rhizosphere, 2025)

Toxicological investigations of biosynthesized nickel ferrites nanoparticles on midgut epithelium of Blaps polychresta as nanopesticides: Structural damages and oxidative stress - Esraa A. Arafat; Abdelazeem S. Eltaweil; Eman M. Abd El-Monaem; Hanan I. Elhenawy; Hussein K. Hussein; Mohamed A. Hassan; Lamia M. El-Samad (Pesticide Biochemistry and Physiology, 2025)

Experimental and numerical investigation of RC deep beams strengthened in shear using NSM-CFRP bars technique with and without steel stirrups - Mohanad Hatem Shadhar; Douread Raheem Hassen; Yasser M. Kadhim; Alaa Salahuddin Araibi; Omar R. Khaleel; Bilal Muiassar M. Salih; Abdul Aziz Abdul Samad; Malik M. Mohammed; Hayder A. Alalwan (Innovative Infrastructure Solutions, 2025)

The Gastroprotective Effects of Salvia indica L. and Selenium In Vivo Study - Talal Salem Al-Qaisi; Ahmed A. J. Jabbar; Mohammed M. Hussein M. Raouf; Parween Abdul-Samad Ismail; Ramzi A. Mothana; Hanan M. Al-Yousef; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Musher Ismael Saleh; Mohammed Awad; Mohamad Fawzi Mahomoodally (Biological Trace Element Research, 2025)

Detection of Paecilomyces formosus in wood-boring beetles associated with oak dieback and decline in the Zagros forests of Iran - Gelareh Ghaderi; Samad Jamali; Robert A. Haack; Jabbar Valipour (Journal of Pest Science, 2025)

Foliar Nourishment with Different Potassium Sources to Maximize Yield Through Improving Nutrient Uptake in Citrus Aurantifolia Trees Grown in Potassium-Deficient Soil - Ahmed A. M. Awad; Hamdy A. Z. Hussein; Asmaa G. A. Abd El Samad; Hussein E. E. Belal; Hamada R. Beheiry (Journal of Soil Science and Plant Nutrition, 2024)
Purpose: Based on its crucial regulatory role in several biochemical processes, potassium (K) is considered to greatly influence fruit yield and quality. Methods: Two field experiments were carried out in two seasons (2021 and 2022) to explore the response of lemon (Baladi cv.) trees grown in K-deficient soil to four different K fertilizer sources applied individually as a foliar spray. K citrate (KC 1 = 1.3 vs. KC 2 = 2.6 g L − 1 ), K nitrate (KN 1 = 1.5 vs. KN 2 = 3.0 g L − 1 ), K tartrate (KT 1 = 1.5 vs. KT 2 = 3.0 g L − 1 ), and K thiosulfate (KS 1 = 1.25 vs. KS 2 = 2.5 g L − 1 ) were applied three times, and the treated trees were compared with untreated trees. This study was established with a randomized complete block design (RCBD) using four replicates. Results: The findings revealed that the KC treatment, regardless of dosage, showed clear superiority in terms of the values for the leaf phosphorus (%), manganese, and zinc contents (mg kg − 1 ), as well as fruit firmness, fruit dry matter, and total soluble solids in both seasons. In second place was the KT treatment, which yielded the best values for fruit length and width in 2021, the best values for leaf nitrogen and iron contents and fruit weight and volume in 2022, and the best values regarding variable fluorescence by maximum fluorescence, relative chlorophyll content (SPAD readings), the photosynthetic performance index, total acidity, and vitamin C in both seasons. Furthermore, the highest total lemon yield and leaf potassium contents were achieved with the KN treatment in both seasons. The heat map illustrating that most of the studied characteristics were positively and significantly correlated with total lemon yield (TLY). Conclusions: The KN treatment, closely followed by the KC treatment, is regarded to be the best treatment for most of the studied trails.

Fulvic and Salicylic Acids Improve Morpho-Physio-Biochemical Attributes, Yield and Fruit Quality of Two Mango Cultivars Exposed to Dual Salinity and Heat Stress Conditions - Asmaa G. A. Abdel Samad; Ahmed Shaaban (Journal of Soil Science and Plant Nutrition, 2024)
Purpose The present research’s main objective was to explore the potential stimulative effect of fulvic acid (FA) as a soil conditioner and salicylic acid (SA) as foliar spraying on morpho-physio-biochemical attributes, fruit yield, and quality of ‘Sediek’ and ‘Ewais’ mango cultivars (cvs.) grown under saline calcareous soil and heat stress conditions Methods Eight treatments, namely, 200 (FA 200 ) and 400 (FA 400 ) g FA tree −1 as a soil addition, 200 (SA 200 ) or 400 (SA 400 ) mg SA L −1 as foliar spraying, and their bilateral combinations (e.g., FA 200 + SA 200 , FA 200 + SA 400 , FA4 00 + SA 200 , and FA 400 + SA 400 ) compared to untreated control on morpho-physio-biochemical attributes, yield, and fruit quality of ‘Sediek’ and ‘Ewais’ mango cvs. grown under saline calcareous soil and heat stress conditions were assessed. These treatments were carried out using a split-plot arrangement in a randomized complete block design replicated three times during the 2022 and 2023 seasons. Results Cultivar Sediek had higher SPAD value, leaf proline and phenolic content, leaf area, fruit weight, yield and vitamin C than Ewais which had higher tree water status and shoot length. Saline calcareous and heat-stressed mango trees without FA or/and SA treatment had a significant decline in their water status, photosynthetic traits, biochemical responses that adversely affected growth and yield and fruit quality. However, soil FA addition and foliar SA spraying alone or in combination at any application level attenuated the negative effects of saline calcareous and heat-stress conditions via enhancing the morpho-physio-biochemical attributes, positively reflecting in tree growth, yield, and fruit quality. FA treatment alone improved tree water status (membrane stability index; MSI and relative water content; RWC), photosynthetic traits (SPAD value and maximum photochemical efficiency; F v /F m ), leaf area, fruit weight, fruit yield, and fruit vitamin C (fruit vit.C), while SA treatment alone enhanced leaf proline and phenolic content, shoot length, and fruit total soluble solids (fruit TSS) compared to the non-FA or SA-treated control. Moreover, co-application of FA 400 and SA 400 effectively alleviated the harmful impacts of dual stress of heat and salinity on mango trees by improving MSI, RWC, SPAD value, F v /F m , proline and phenolic content, fruit weight, fruit yield, fruit TSS, fruit vit.C by 19.7, 26.1, 46.7, 18.7, 101.7, 390.7, 42.7, 6.8, 22.6, 69.6% (averages of the two seasons), respectively, compared to the non-FA or SA-treated trees. Conclusion It is recommended to add 400 g FA tree −1 to soil integrated with 400 mg SA L −1 foliar spraying four times at 30-day intervals for improving water status and photosynthetic traits, proline and phenolic accumulation, thereby growth, yield, and fruit quality of mango trees exposed to dual stress of heat and salinity under arid conditions.

Efficacy of propolis and royal jelly in attenuating cadmium-induced spermatogenesis and steroidogenesis dysregulation, causing infertility in rats - Alaa Amr; Ahmed E. Abdel Karim; Maria Augustyniak; Abeer El Wakil; Lamia M. El-Samad; Mohamed A. Hassan (Environmental Science and Pollution Research, 2024)

Cowpea leaf and pod spots caused by Periconia igniaria and their potential control using biosynthesized zinc oxide and magnesium oxide nanoparticles - Faten H. Y. Abdel-Samad; Qi Huang; Marzouk R. Abdel-Latif; Zekry A. Shehata; Hanaa A. H. Armanyous; Abdelmonim Ali Ahmad (Journal of Plant Pathology, 2024)
Cowpea is subject to attacks by a wide range of plant pathogens including bacteria, fungi, viruses, and nematodes. In this study, a field survey was conducted in cowpea growing regions of El-Minya Governorate of Egypt including Minya, Beni Mazar and Maghagha districts for leaf and pod spot disease. Our results revealed that the disease was present in all surveyed fields with the highest disease incidence and severity found in Minya District. For the first time in Egypt, the causal agent of the disease was determined to be Periconia igniaria based on morphology of the fungal isolates, internal transcribed spacer sequence homology to a P. igniaria strain, and fulfillment of Koch’s postulates. To explore control measures, zinc oxide (ZnO) and magnesium oxide (MgO) nanoparticles (NPs) were synthesized biologically using green coffee extract. Both NPs were characterized, and their formulations confirmed using scanning electron microscopy and the energy spectrum dispersion analysis. The biosynthesized ZnO- and MgO-NPs were demonstrated to have antifungal activity against in vitro mycelium growth of P . igniaria at all tested concentrations from 25 to 200 ppm, and ZnO NPs were more effective than MgO NPs at the same concentration. When 100 ppm of ZnO NPs was tested in planta , it significantly reduced disease incidence and severity in detached cowpea leaves and pods under laboratory conditions, and in cowpea plants under greenhouse conditions. Our results demonstrated that the biosynthesized ZnO NPs have great potential to be developed into an effective and eco-friendly control method against cowpea disease caused by P. igniaria.

Astaxanthin supplementation ameliorates simulated heat stress by regulating physio-biochemical responses in Sirohi goats - Priyanka M. Kittur; K. Karthiga; Lipika Sarma; Anjali V. K. Gururaj; Kant Lata; V. Verma; H. A. Samad; V. S. Chouhan; Gyanendra Singh; V. P. Maurya (Veterinary Research Communications, 2024)

Earthworm cast microbiomes differ across soil types in northern forests - Justine D.M. Lejoly; Sylvie A. Quideau; Jérôme Laganière; Justine Karst; Christine Martineau; Abdul Samad (Applied Soil Ecology, 2024)

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

Population exposure to emerging perfluoroalkyl acids (PFAAs) via drinking water resources: Application of multivariate statistics and risk assessment models - Kifayatullah Khan; Muhammad Younas; Jafar Ali; Noor Samad Shah; Yasar N. Kavil; Mohammed A. Assiri; Xianghui Cao; Hassan Sher; Afsheen Maryam; Yunqiao Zhou; Muhammad Yaseen; Li Xu (Marine Pollution Bulletin, 2024)

Nanoparticles—mediated entomotoxicology: lessons from biologica - Lamia M. El-Samad; Nahed R. Bakr; Mohamed Abouzid; Eslam S. Shedid; John P. Giesy; Shaden A. M. Khalifa; Hesham R. El-Seedi; Abeer El Wakil; Yahya Al Naggar (Ecotoxicology, 2024)

Physiological and Agronomic Responses and Nutrient Uptake of Soybean Genotypes Cultivated Under Various Sowing Dates - Mostafa G. Shahin; Hani S. Saudy; Mohamed E. El-Bially; Wasfi R. Abd El-Momen; Yasser A. El-Gabry; Gomaa A. Abd El-Samad; Amany N. Sayed (Journal of Soil Science and Plant Nutrition, 2023)
Late or early sowing subjecting crop plants to stress conditions, this is simulating the climatic change effects. The global warming and climate change are critical issues in agriculture since progressive rise in temperature leads to exposure the crops to heat stress, hence low productivity. Since weather conditions are uncontrollable, it is impossible to modulate their negative impacts against crop growth and development. However, scientists should not be handcuffed about this serious problem. So, in open field conditions, the performance of some soybean genotypes was evaluated under different sowing dates. Along the two seasons of 2019 and 2020, field experiments were designed in a split-plot design using three replicates to evaluate the performance of four soybean genotypes (Giza-21, Giza-35, Giza-111, and Crawford) under four sowing dates (15th April, 30th April, 15th May, and 30th May). Various physiological and growth traits, yield attributes, seed nutrient contents, and oil and protein contents were estimated. Sowing Crawford (in both seasons) and Giza-35 (in the first season) on 15th April as well as Giza-111 either on 30th April or 15th May produced the highest catalase activity. In plots sown on 30th April, Crawford and Giza-21 (in the first season) and Giza-111 (in both seasons) exhibited the highest leaves area plant −1 . Plots sown by Giza-111 on 30th April was the potent interaction for enhancing seed yield in both seasons. Under any sowing date in the second season and the sowing date of 30th April in the first season, Giza-111 was the effective genotype for recording the maximum seed oil content. For adopting a specific stress condition scenario, it is advisable to insert Giza-111 as an effective gene pool to improve soybean genotypes under unfavorable conditions, expressed in sowing dates.

Air pollution prediction using machine learning techniques – An approach to replace existing monitoring stations with virtual monitoring stations - A. Samad; S. Garuda; U. Vogt; B. Yang (Atmospheric Environment, 2023)

A combination of host ecology and habitat but not evolutionary history explains differences in the microbiomes associated with rotifers - Ester M. Eckert; Tommaso Cancellario; Paul L. E. Bodelier; Steven A. J. Declerck; Liang Diwen; Sainur Samad; Monika Winder; Libin Zhou; Diego Fontaneto (Hydrobiologia, 2023)
The holobiont concept places emphasis on the strict relationship between a host and its associated microbiome, with several studies supporting a strong effect of the quality of the microbiome on the host fitness. The generalities of the holobiont have been questioned for several invertebrates, including zooplankton. Here we assess the role of host ecology, habitat, and evolutionary history to explain the differences in the microbiomes associated with rotifers, across a broad taxonomic spectrum and from different habitats. The analyses of 93 rotifer-associated microbiomes from 23 rotifer host species revealed that a combination of effects from the host ecology and its habitat seem to be stronger than host phylogenetic distances in explaining differences in microbial composition of the microbiomes. This pattern is in line with the idea of habitat filtering being a stronger explanation than co-evolution in shaping the relationship between a microbiome and its rotifer host.

Switchable hepatic organelles aberrations in DEN-induced mice under the influence of chemically characterized silk sericin - Basant A. Bakr; Ismail A. Sadek; Lamia M. El-Samad; Abeer El Wakil (Tissue and Cell, 2023)

Thyroid hormone dynamics of Tharparkar and Sahiwal cattle during induced heat stress - Anjali; Gururaj VK; Lipika Sarma; M. Tripathi; Med Ram Verma; Vinay Verma; M. C. Pathak; H. A. Samad; V. P. Maurya; V. S. Chouhan; Gyanendra Singh (Tropical Animal Health and Production, 2023)

Two new root endophyte and nematode cyst parasite species of the widely distributed genus Laburnicola - Dániel G. Knapp; Galiya K. Akhmetova; Gábor M. Kovács; Abdelfattah A. Dababat; Wolfgang Maier; Samad Ashrafi (Mycological Progress, 2022)
Fungal root endophytes, including the common form group of dark septate endophytes (DSEs), represent different taxonomic groups with potentially diverse life strategies. During surveys of DSE communities and of nematode cysts colonizing fungi, isolates representing Laburnicola ( Didymosphaeriaceae , Pleosporales ) lineages were discovered. Here we carried out a comprehensive study of the phylogenetic relationships and taxonomy of fungi collected from plant roots in Hungary, Mongolia, and Kazakhstan and from eggs of the cereal cyst nematode Heterodera filipjevi in Turkey. In addition to the study of the morphology and culture characteristics of the strains, four loci (internal transcribed spacer, partial large and small subunit regions of nuclear ribosomal DNA and partial translation elongation factor 1-alpha) were used to infer the molecular phylogenetic relationships of the strains within Laburnicola . The isolates were found to represent two distinct lineages, which are described here as novel species, Laburnicola nematophila and L. radiciphila . The interaction of the strains with plants and nematodes was examined using in vitro bioassays, which revealed endophytic interactions with the plant roots and parasitic interactions with the nematode eggs. Analyses of similar ITS sequences found in public databases revealed that members of the genus Laburnicola are widely distributed characteristic members of the plant microbiome, and they are reported as parasites of plant parasitic cyst nematodes here for the first time.

High prevalence of vancomycin non-susceptible and multi-drug resistant enterococci in farmed animals and fresh retail meats in Bangladesh - Mohammed A. Samad; Md Shahjalal Sagor; Muhammad Sazzad Hossain; Md Rezaul Karim; Mohammad Asheak Mahmud; Md Samun Sarker; Fahria A. Shownaw; Zakaria Mia; Roderick M. Card; Agnes Agunos; Lindahl Johanna (Veterinary Research Communications, 2022)

Reserpine-induced altered neuro-behavioral, biochemical and histopathological assessments prevent by enhanced antioxidant defence system of thymoquinone in mice - Noreen Samad; Natasha Manzoor; Zahra Muneer; Sheraz A. Bhatti; Imran Imran (Metabolic Brain Disease, 2021)

A Review of Bacterial Antibiotic Resistance Genes and Their Removal Strategies from Wastewater - Zainura Zainon Noor; Zainab Rabiu; Mohd. Helmi Mohd. Sani; Abdul Fatah A. Samad; Mohd. Farizal Ahmad Kamaroddin; María Florencia Perez; Julian Rafael Dib; Huma Fatima; Rajeshwari Sinha; Sunil Kumar Khare; Zainul Akmar Zakaria (Current Pollution Reports, 2021)

Bacterial Reduction of Cr(VI): Operational Challenges and Feasibility - Wan Azlina Ahmad; Chidambaran Kulandaisamy Venil; Evans M. Nkhalambayausi Chirwa; Yi-Tin Wang; Mohd. Helmi Sani; Abdul Fatah A. Samad; Mohd. Farizal Ahmad Kamaroddin; Edgardo R. Donati; Maria Sofia Urbieta; Zainul Akmar Zakaria (Current Pollution Reports, 2021)

Comparative Study on Bone Marrow-Versus Adipose-Derived Stem Cells on Regeneration and Re-Innervation of Skeletal Muscle Injury in Wistar Rats - Manal H. Moussa; Ghada G. Hamam; Asmaa E. Abd Elaziz; Marwa A. Rahoma; Abeer A. Abd El Samad; Dalia A. A. El-Waseef; Mohamed A. Hegazy (Tissue Engineering and Regenerative Medicine, 2020)

Coronavirus pandemic (COVID-19) and its natural environmental impacts - P. F. Rupani; M. Nilashi; R. A. Abumalloh; S. Asadi; S. Samad; S. Wang (International Journal of Environmental Science and Technology, 2020)

Influence of weather patterns and air quality on ecological population dynamics of ectoparasites in goats - Y. Ajith; U. Dimri; E. Madhesh; A. Gopalakrishnan; Med Ram Verma; H. A. Samad; K. K. Reena; A. K. Chaudhary; G. Devi; J. Bosco (International Journal of Biometeorology, 2020)

Exposure to Lead (Pb) Induced Changes in the Metabolite Content, Antioxidant Activity and Growth of Jatropha curcas (L.) - Amal A. A. Mohamed; Mahmoud H.O. Dardiry; Abdul Samad; Eman Abdelrady (Tropical Plant Biology, 2020)

Assessing the economic value of urban green spaces in Kuala Lumpur - Nur Syafiqah A. Samad; Abdul Samad Abdul-Rahim; Mohd Johari Mohd Yusof; Katsuya Tanaka (Environmental Science and Pollution Research, 2020)

Alpha lipoic acid supplementation ameliorates the wrath of simulated tropical heat and humidity stress in male Murrah buffaloes - H. A. Samad; Y. Y. Konyak; S. K. Latheef; A. Kumar; I. A. Khan; V. Verma; V. S. Chouhan; M. R. Verma; V. P. Maurya; Puneet Kumar; M. Sarkar; G. Singh (International Journal of Biometeorology, 2019)

Hypolipidemic effect of novel 2,5-bis(4-hydroxybenzylidenamino)-1,3,4-thiadiazole as potential peroxisome proliferation-activated receptor-α agonist in acute hyperlipidemic rat model - Lama A. Hamadneh; Dima A. Sabbah; Suhair J. Hikmat; Luma A. Al-Samad; Mariam Hasan; Tariq M. Al-Qirim; Imad M. Hamadneh; Ammar H. Al-Dujaili (Molecular and Cellular Biochemistry, 2019)

Isoenzymes and protein polymorphism in Blaps polycresta and Trachyderma hispida (Forsskål, 1775) (Coleoptera: Tenebrionidae) as biomarkers for ceramic industrial pollution - Dalia A. Kheirallah; Lamia M. El-Samad (Environmental Monitoring and Assessment, 2019)

Amendment of Caulerpa sertularioides marine alga with sulfur-containing materials to accelerate Cu removal from aqueous media - Bahman Ramavandi; Sina Dobaradaran; Fatemeh Papari; George A. Sorial; Ahmad Ebrahimi; Leila Madeh Khaksar; Samad Akbarzadeh; Seyedenayat Hashemi; Fatemeh Teimori (Environmental Science and Pollution Research, 2019)

Response to nitrogen addition reveals metabolic and ecological strategies of soil bacteria - Md Sainur Samad; Charlotte Johns; Karl G. Richards; Gary J. Lanigan; Cecile A. M. de Klein; Timothy J. Clough; Sergio E. Morales (Molecular Ecology, 2017)
The nitrogen (N) cycle represents one of the most well‐studied systems, yet the taxonomic diversity of the organisms that contribute to it is mostly unknown, or linked to poorly characterized microbial groups. While new information has allowed functional groups to be refined, they still rely on a priori knowledge of enzymes involved and the assumption of functional conservation, with little connection to the role the transformations, plays for specific organisms. Here, we use soil microcosms to test the impact of N deposition on prokaryotic communities. By combining chemical, genomic and transcriptomic analysis, we are able to identify and link changes in community structure to specific organisms catalysing given chemical reactions. Urea deposition led to a decrease in prokaryotic richness, and a shift in community composition. This was driven by replacement of stable native populations, which utilize energy from N‐linked redox reactions for physiological maintenance, with fast responding populations that use this energy for growth. This model can be used to predict response to N disturbances and allows us to identify putative life strategies of different functional and taxonomic groups, thus providing insights into how they persist in ecosystems by niche differentiation.

Molecular identification of Chilli leaf curl India virus along with betasatellite molecule causing leaf curl disease of menthol mint (Mentha arvensis var. Kosi) in India - Sana Tabanda Saeed; B. Kumar; A. K. Shasany; A. Samad (Journal of General Plant Pathology, 2017)

Biochemical and histological biomarkers in the midgut of Apis mellifera from polluted environment at Beheira Governorate, Egypt - Ahmed M. Abu El-Saad; Dalia A. Kheirallah; Lamia M. El-Samad (Environmental Science and Pollution Research, 2017)

The importance and management strategies of cereal cyst nematodes, Heterodera spp., in Turkey - Abdelfattah A. Dababat; Mustafa Imren; Gul Erginbas-Orakci; Samad Ashrafi; Elif Yavuzaslanoglu; Halil Toktay; Shree R. Pariyar; Halil I. Elekcioglu; Alexei Morgounov; Tesfamariam Mekete (Euphytica, 2015)

Nuclear DNA C-values for biodiversity screening: Case of the Lebanese flora - M. Bou Dagher-Kharrat; N. Abdel-Samad; B. Douaihy; M. Bourge; A. Fridlender; S. Siljak-Yakovlev; S. C. Brown (Plant Biosystems, 2013)

Comparative In Silico–In Vivo Evaluation of ASGP-R Ligands for Hepatic Targeting of Curcumin Gantrez Nanoparticles - Anisha A. D’Souza; Puneet Jain; C. N. Galdhar; Abdul Samad; Mariam S. Degani; Padma V. Devarajan (The AAPS Journal, 2013)

Molecular identification of a phytoplasma associated with Ajwain (Trachyspermum ammi) in India - A. Samad; S. Panda; Mahesh K. Gupta; P. V. Ajayakumar; Ashutosh K. Shukla (European Journal of Plant Pathology, 2011)

Regeneration of phytoplasma-free Artemisia roxburghiana Besser var. purpurascens (Jacq.) Hook. plants using apical meristem culture - Suchitra Banerjee; Flora Haider; G. D. Bagchi; A. Samad (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

A tymovirus from Calopogonium mucunoides in Malaysia is not clitoria yellow vein tymovirus - A. J. Gibbs; A. M. Mackenzie; N. Abdul-Samad (Archives of Virology, 1997)